Reference of Discourse Analysis in “Thor: Ragnarok” Movie - Mandela Putri Salsabila; Ervina CM Simatupang (Ethical Lingua: Journal of Language Teaching and Literature, 2022)
The purposes of this study are to analyze the function of reference and find which reference occurs the most in “Thor: Ragnarok” movie. The research used qualitative descriptive method, the data was obtained from the Script Slug website and the official streaming platform Disney+. In analyzing the data, this research uses discourse analysis theory from Wodak and Krzyzanowski (2008). As the results this research shows there are 30 references found in “Thor: Ragnarok” movie. The data that contains references are categorized into 3 types of reference. All the references that have been found are as the following distribution: 16 (53,3%) data for exophoric reference, 9 (30%) anaphoric reference, and 5 (16,6%) data for cataphoric. In conclusion, the most reference occurs in the “Thor: Ragnarok” movie is exophoric reference. Reference has different function based on the topic and the use of reference in sentences. On the other hand, reference can give more explanation for the topic, and replace the word without changing its meaning.